The Little Data Book on Financial Development 2013 - World Bank (Washington, DC: World Bank, 2012)
The little data book on financial development 2013 is a pocket edition of the global financial development database published as part of the work on the global financial development report 2013: rethinking the role of the state in finance. The global financial development database is an extensive dataset of financial system characteristics for 203 economies. The database includes measures of (1) size of financial institutions and markets (financial depth), (2) degree to which individuals can and do use financial services (access), (3) efficiency of financial intermediaries and markets in intermediating resources and facilitating financial transactions (efficiency), and (4) stability of financial institutions and markets (stability). There is ample evidence on the role financial sector development plays in economic development, poverty alleviation and economic stability. However there are serious shortcomings associated with measuring the concept of the 'functioning of the financial system.' Recognizing the need for good data to better understand the concept of financial development, the World Bank's financial and private sector Vice Presidency and development economics Vice Presidency have recently launched a global financial development database, an extensive worldwide database that combines and updates several financial data sets. The data highlight the multi-dimensional nature of financial systems. Deep financial systems do not necessarily provide high degrees of financial access; highly efficient financial systems are not necessarily more stable than the less efficient ones, and so on. Each of these characteristics has an association with aspects of the broader socio-economic development, and each is, in turn, strongly associated with financial sector policies and other parts of the enabling environment for finance. The data also demonstrate the effects of the global financial crisis. The crisis not only increased financial instability but also translated into difficulties along other dimensions, such as increasing problems of access to financial services.